Hepatic steatosis and patients with inflammatory bowel disease: when transient elastography makes the difference - Arieira, Cátia (2019)
Recent studies suggest an increased prevalence of hepatic steatosis (HS) in patients with inflammatory bowel disease (IBD). Features such as chronic inflammation, previous surgeries, drug-induced hepatotoxicity, malnutrition, and intestinal dysbiosis seem to be involved in its pathogenesis. Background Recent studies suggest an increased prevalence of hepatic steatosis (HS) in patients with inflammatory bowel disease (IBD). Features such as chronic inflammation, previous surgeries, drug-induced hepatotoxicity, malnutrition, and intestinal dysbiosis seem to be involved in its pathogenesis. Aims The aim of this study was to assess the frequency of HS in patients with IBD quantified by controlled attenuation parameter (CAP) and by clinical–analytical scores: Hepatic Steatosis Index (HSI) and Fatty Liver Index (FLI). The secondary aim was to investigate risk factors associated with HS in patients with IBD. Patients and methods A cross-sectional study was carried out including consecutive outpatients observed in our department between January and March 2017. HS was defined as HSI of at least 36 or FLI of at least 60 or CAP of greater than 248. Results A total of 161 patients were included, with a mean age of 40.6±12.8 years. There were 86 (53.4%) female patients. Overall, 62.7% had Crohn’s disease and 37.1% had ulcerative colitis. Moreover, 73 (45.3%) patients had CAP greater than 248, 27 (16.8%) had FLI greater than 60, and 46 (28.6%) had HSI greater than 36. We found that patients with CAP of greater than 248 were more frequently obese (28.8 vs. 0.0% P<0.001), male (57.5 vs. 37.5% P=0.011), and presented more frequently with metabolic syndrome (23.9 vs. 4.5% P <0.001). With regard to IBD factors, patients with HS had a higher frequency of previous surgeries (31.5 vs. 12.5% P=0.003). In multivariate analysis, only male sex [odds ratio: 5.7 (95% confidence interval: 2.0–15.9); P=0.001] and previous surgeries [odds ratio: 5.9 (95% confidence interval: 1.5–22.9); P=0.011] were independent risk factors of HS. Conclusion In our cohort, the frequency of HS varied between 16.8 and 45.3% defined by noninvasive methods. We found that male sex and previous history of surgery were the independent risk factors of HS when quantified by transient elastography.